Basic English Teaching for Fostered Children of Youth Organization in Cimanggis Subdistrict, Depok City - Sriwartini, Yayu; Febriyani, Dina Iqomah; Dewi, Charmanintha Putrista; Parniati, Nur Hanifah Putri; Pradita, Lusiana Indah (Indonesian Journal of Community Services Cel, 2023)
Basic English teaching activities were conduced on December 20, 2020 at RT 04, Cimanggis Subdistrict, Depok City, West Java through the cooperation of the local youth organization, and were attended by 20 children as the participants. This community services activity was conducted with aim to improve the children’ pronounciation quality of English words and increase their vocabulary mastery. To find out the participants' English skills, firstly the community services team (teachers) conducted a pre-test. After that, the learning was implemented using direct learning methods, card games, guessing words, and guessing sentences. The result showed that among 20 participants, 15 children were able to correctly pronounce the 5 words they chose. In the meaning understanding test, among 20 learning participants, as many as 7 children (35%) were able to name 10 pictures they took in English, 4 children (20%) were only able to name 9 pictures, 6 children (30%) were able name 8 pictures correctly, and 3 children (15%) were able to name 7 pictures correctly. In conclusion, the implementation of this basic English teaching program was declared successful according to the achievement target. This can be seen from the increase in knowledge among the participants, namely the increase in vocabulary mastery and knowledge of the correct pronunciation of the words introduced in the teaching.